Effects of ion concentration and solvent composition on the properties of water-methanol solutions of NaCl. NPT molecular dynamics computer simulation results - Cruz Sanchez, M.; Gujt, J.; Sokolowski, S.; Pizio, O. (Condensed Matter Physics, 2018)
Isothermal-isobaric molecular dynamics simulations are used to examine the microscopic structure and other
properties of a model solution consisting of NaCl salt dissolved in water-methanol mixture. The SPC/E water
model and the united atom model for methanol are combined with the force field for ions by Dang [J. Amer.
Chem. Soc., 1995, 117, 6954] to describe the entire system. Our principal focus is to study the effects of two
variables, namely, the solvent composition and ion concentrations on the solution’s density, on the structural
properties, self-diffusion coefficients of the species and the dielectric constant. Moreover, we performed a detailed analysis of the first coordination numbers of the species. Trends of the behaviour of the average number
of hydrogen bonds between solvent molecules are evaluated. Для дослiдження мiкроскопiчної структури та iнших властивостей модельного розчину, що складається
з солi NaCl, розчиненої у сумiшi води та метанолу, використано iзотермiчно-iзобаричне моделювання
методом молекулярної динамiки. Щоб описати всю систему, модель води SPC/E i модель еквiвалентного атома для метанолу поєданi iз силовим полем для iонiв згiдно з Дангом [ J. Amer. Chem. Soc., 1995,
117, 6954]. Нашою головною метою є дослiдження впливу двох змiнних, а саме, складу розчинника та
концентрацiї iонiв на густину розчину, на структурнi властивостi, на коефiцiєнти самодифузiї сортiв та на
дiелектричну сталу. Крiм того, здiйснено детальний аналiз перших координацiйних чисел сортiв. Визначено тенденцiї поведiнки середньої кiлькостi водневих зв’язкiв.